(untitled) (Itinera, 2017)
In all his performances Joël Pommerat is writing a theatre of trouble, by its nature addressed to the spectators’ senses. Thanks to the example of Au Monde (2004), it will be shown how trouble is produced by the hiatus between sight and hearing, visual half-light and auditive acuteness, but also by the almost obsessional questioning of senses all over the text. How do senses and sensations build the meaning of play Au monde ? This paper offers a study their visual and lexical occurrences.